2020
DOI: 10.1002/jsfa.10345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPPU on bulk optical properties of kiwifruit during storage in near‐infrared range

Abstract: BACKGROUND Investigating the effect of N‐(2‐chloro‐4‐pyridyl)‐N′‐phenylurea (CPPU) on the bulk optical properties of postharvest kiwifruit is helpful in understanding the mechanism of identification of CPPU‐treated kiwifruit using spectroscopy and to develop effective optical sensing techniques. In this study, the absorption coefficient μa and reduced scattering coefficient μs′ of flesh and skin of kiwifruit treated with CPPU solutions at CPPU concentration levels (CCLs) of 0, 5, 10 and 15 mg L−1 were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In contrast, fruit storage time and the (846 nm) of the same fruit that was negatively correlated (the longer the time, the lower the ) for both storage conditions. Numerous research investigations have demonstrated a correlation between the properties of fruit and textural attributes, including factors like firmness, cell size, and so on 31 , 51 . In the present study, the values and firmness of kiwifruit flesh exhibited a simultaneous reduction over the storage period.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, fruit storage time and the (846 nm) of the same fruit that was negatively correlated (the longer the time, the lower the ) for both storage conditions. Numerous research investigations have demonstrated a correlation between the properties of fruit and textural attributes, including factors like firmness, cell size, and so on 31 , 51 . In the present study, the values and firmness of kiwifruit flesh exhibited a simultaneous reduction over the storage period.…”
Section: Resultsmentioning
confidence: 99%
“…The differences of optical properties between non-bruised apple tissues and bruised ones can be directly used for early-stage bruise detection. It is well known that there are quite a lot of optical property measuring methods, e.g., timeresolved, spatially resolved, and integrating sphere, which have been employed for measuring optical properties of diverse agro-food products [8][9][10][11]. However, they are generally limited to point measurement and cannot attain depth-resolved information, resulting in great challenges in the nondestructive detection of early-stage bruises of apples [12,13].…”
Section: Introductionmentioning
confidence: 99%